2018
DOI: 10.1088/1361-6528/aad64c
|View full text |Cite
|
Sign up to set email alerts
|

Engineering synaptic characteristics of TaOx/HfO2 bi-layered resistive switching device

Abstract: We performed various pulse measurements on an atomic layer deposited (ALD) HfO-based resistive switching random access memory (RRAM) device and investigated its electronic synaptic characteristics. Unlike requirements for RRAM device application, to achieve the multi-state conductance changes required for the synaptic device, we employed additional sputtered TaO thin film formation on the ALD HfO switching medium, which leads to engineering the concentration of oxygen vacancies and modulating the conductive fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 36 publications
2
32
2
1
Order By: Relevance
“…Next, the possible switching mechanism of pseudo-interface-type switching is discussed ( Figure 4 ). We match the I-V curve according to voltage and polarity to the switching model by referring to the existing models for HfO 2 and TaO x in Figure 4 a [ 24 , 25 , 26 , 27 , 28 , 29 ]. When a negative bias is applied to the top electrode in the initial state, it is divided into the HfO 2 and TaO x layers in Figure 4 b.…”
Section: Resultsmentioning
confidence: 99%
“…Next, the possible switching mechanism of pseudo-interface-type switching is discussed ( Figure 4 ). We match the I-V curve according to voltage and polarity to the switching model by referring to the existing models for HfO 2 and TaO x in Figure 4 a [ 24 , 25 , 26 , 27 , 28 , 29 ]. When a negative bias is applied to the top electrode in the initial state, it is divided into the HfO 2 and TaO x layers in Figure 4 b.…”
Section: Resultsmentioning
confidence: 99%
“…Memristive synapses with a similar working mechanism have been realized in IGZO x /IGZO y , HfO x /CeO x , TaO x /TaO y , TaO x /AlO x , TaO x /TiO 2 , TaO x /HfO 2 , TiO x /AlO x , MoO x /MoS 2 , and Al 2 O 3 /Nb x O y bilayer structures . It has been speculated that compared to synaptic devices composed of a single oxide layer, memristive synapses based on a bilayer structure possess more reliable performance due to controllable formation/rupture of conducting filament at the vicinity of the interface between these two layers (see Figure ) . This speculation is, to some extent, in accord with the idea proposed in ref.…”
Section: Working Mechanisms Of Memristive Synapsesmentioning
confidence: 99%
“…Schematic illustration of the memristive switching mechanisms between a) HfO 2 single‐layer and b) HfO 2 /TaO x bilayer memristive synapses. All panels reproduced with permission . Copyright 2018, IOP Publishing Ltd.…”
Section: Working Mechanisms Of Memristive Synapsesmentioning
confidence: 99%
“…Such devices could gradually change the conductance of the path of current according to input voltage pulses, [16,[21][22][23][24][25][26][27] thereby allowing for the implementation of the functional operation of a synapse within a unit device. [28,29] Recently, HfO x -, [30] TaO x -, [31,32] or TiO x - [33,34] based ReRAM devices and Ge 2 Sb 2 Te 5 - [16,35,36] or Mott-insulator- [37] based PCRAM devices have successfully emulated synaptic dynamics, such as LTP/ LTD characteristics and excitatory/inhibitory postsynaptic currents (EPSC/IPSC). [28,29] Recently, HfO x -, [30] TaO x -, [31,32] or TiO x - [33,34] based ReRAM devices and Ge 2 Sb 2 Te 5 - [16,35,36] or Mott-insulator- [37] based PCRAM devices have successfully emulated synaptic dynamics, such as LTP/ LTD characteristics and excitatory/inhibitory postsynaptic currents (EPSC/IPSC).…”
mentioning
confidence: 99%
“…In particular, studies on memristive synapses have demonstrated that high‐density HNNs can be constructed via fabrication in a crossbar point array structure . Recently, HfO x ‐, TaO x ‐, or TiO x ‐ based ReRAM devices and Ge 2 Sb 2 Te 5 ‐ or Mott‐insulator‐ based PCRAM devices have successfully emulated synaptic dynamics, such as LTP/LTD characteristics and excitatory/inhibitory postsynaptic currents (EPSC/IPSC). Prezioso et al fabricated a neural network based on an Al 2 O 3 /TiO 2 x memristor crossbar point array and demonstrated successful pattern classification of 3 × 3 binary images.…”
mentioning
confidence: 99%